(untitled) (Nexo Revista Científica, 2021)
The paper explores the topical subject of modeling enterprise operations with the use of marginal analysis. The market economy is characterised by the heightened instability of the complex socioeconomic system, which is almost impossible to fully grasp and study. Businesses face intense competition. Adequate managerial decision-making requires in-depth comprehensive assessments of the situation and reliable forecasting. A firm that makes correct forecasts gains additional profit compared to one abstaining from forecasting. Meanwhile, a firm making an incorrect forecast loses most of all. Managerial decisions often rely on break-even analysis, i. e., marginal analysis. This paper explores examples where even in cases when disadvantageous choices are made (as shown by break-even analysis), the setting can still lead to positive results, i. e., at least a moderate profit, through the validation of the managerial decision by further analysis and calculations. The methods of enquiry, retrospective and document analysis, as well as synthesis, generalisation and systematisation were used.